A human-induced pluripotent stem cell (iPSC) line (SMUSHi006-A) from an ALS patient carrying a mutation c.1126C > T in the FUS gene - Chunyan Huang; Liying Qiu; Wenyan Zhou; Congwen Shao; Xichun Wang; Qiwen Zhang; Weilin Chen; Min Xiong; Min Huang; Mei Tang; Liangyu Zou; Xueqing Xu (Stem Cell Research)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease. Four major genes associated with ALS—SOD1, TARDBP, FUS, and C9orf72—have been identified, with the fused in sarcoma (FUS) gene demonstrating considerable genetic heterogeneity. Our research group has previously established an induced pluripotent stem (iPS) cell line harboring the c.1562G > A mutation in the FUS gene. The objective of this study is to create another iPS cell line featuring the pathogenic c.1126C > T mutation in the FUS gene. This research aims not only to establish a disease model for ALS linked to FUS mutations but also to pave the way for potential therapeutic interventions.